Is Dignity Still Necessary in Health Care? From Definition to Recognition of Human Dignity - Ferdynus, Marcin Paweł (2024)
The concept of dignity is not, as some scholars claim, an unnecessary moral idea, and nor need it have religious overtones or be characterised by speciesism. In this article, I try to show that dignity can be defined and recognised. The starting point for the argumentation is the four typologies of dignity, which show that the term "dignity" can denote significantly different concepts, and that the different concepts of dignity can have significantly different ontological senses. A unified typology of dignity allows for five categories to be distinguished: inherent dignity, dignity based on changeable qualities, moral dignity, bestowed dignity and comportment dignity. I take the first two categories of dignity as the object of the analysis, with which I seek to formulate a philosophical response to the charge of speciesism and to show on what basis it can be maintained that all human beings possess dignity. To this end, I distinguish between existential dignity, actual dignity, and potential dignity. Distinguishing these types of dignity becomes possible in the light of Aquinas' and Aristotle's views. In the final section, I point to two ways of recognising dignity. The first is based on certain narratives and emotional states ("ecumenical model of dignity"), while the second is related to a specific moral experience developed within ethical personalism.
Keywords: Dignity; Ecumenical model of dignity; Moral Experience; Speciesism; Typologies of dignity